Pelatihan Pendidikan Karakter Dalam Ekstrakurikuler Berkuda Di Pondok Pesantren Imam Bukhari, Karanganyar, Jawa Tengah - Permadi, Muhammad; Risnawati, Atin (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2025)
The purpose of this community service is to instill values of discipline, responsibility, courage, patience, and cooperation through physical activities that are religious and educational in nature. The methodology used in this activity is based on a qualitative approach with a case study method, where the implementation process is carried out through observation, interviews, and direct mentoring of students participating in horse riding activities. The results of the activity show that horse riding training has a significant influence on changes in the attitudes and behavior of students. They become more disciplined, resilient, and have a high sense of empathy and responsibility, both towards themselves and their surroundings. Horse riding activities not only build physical strength, but also instill spiritual values through the example of the Prophet Muhammad SAW, who made horse riding a noble sunnah. The novelty of this community service activity lies in the Sunnah-based character education model contextualized in the life of Islamic boarding schools. The integration of Sunnah sports and Islamic character values is an innovation in non-formal learning approaches that touch on the physical, moral, and spiritual aspects of students. The implications for educational policy indicate the need to strengthen Islamic-based extracurricular activities in educational institutions so that character education does not stop at the theoretical level but is also implemented in meaningful real-world activities.